A Translation Analysis Of Noun Phrase In Allegiant Novel Into Allegiant By Nur Aini - NUR HAKIM, CYNTHIA SUSILIA, Dr. Dwi Haryanti, M.Hum, Siti Fatimah, S.Pd, M.Hum (2015)
This research aims at classifying the translation variation of noun phrase, describe acceptability of noun phrase in Allegiant Novel into Allegiant by Nur Aini. This theory applies descriptive qualitative research. The data of this research are Novel of English translation into Indonesian translation. The source of data is Allegiant novel and its translation. The results of the research show that 1) there are 5 types of English noun phrase and 10 types of Indonesian noun phrase in Allegian novel into Allegiant by Nur Aini; 2) the other variations in the Translation English of Noun Phrase into Indonesian Noun Phrase, namely English noun phrase translated into Indonesian Noun, English noun phrase translated into Indonesian Verb, English noun phrase translated into Indonesian Adjective, and English noun phrase translated into Indonesian Adv erb. 3) there are 1126 data analysis from three categories of judgments in acceptance translation language, namely acceptable, less acceptable, and unacceptable.